Linguoculturological Aspect of Language Learning in National Groups - Ernazarova M.N (Genius Publishing Group, 2022)
The article considers a new scientific direction studying the interaction of two semiotic areas - language and culture, and the development of this direction.
Keywords: Linguoculturology; semiotic areas; language; culture